The Influence of Audio Visual Based Learning in Improving Student Learning Outcomes in Elementary Schools - Eriawaty, Eriawaty; Rokhmah, Siti; Aljauhari, Shofwan (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Audio-visual-based learning has become the object of discourse, especially those that focus on discussing development, utilization, and application in the learning process, so discourse regarding the influence of audio-visual-based learning in improving student learning outcomes tends to be neglected in scientific discussions. In line with this, this study focuses on